Computer Geometric Modeling Course for Construction Students - Kheifetc Kheyfets, Alexander L. (2022 VI International Conference on Information Technologies in Engineering Education (Inforino), 2022)
The content of a special computer-graphic course for training construction major students of the SUSU elite group is presented. The topics of lectures and the content of control and graphic tasks are given. The tasks provide for the construction of original models of architectural objects. There is also a task for visualization of surfaces specified by an analytical expression, with programming elements in the AutoLisp language. One of the tasks involves the construction of animation using AutoCAD. All the constructions are performed as photorealistic ones (light, shadows, materials and perspective). Conclusions are made about the positive experience of teaching the course, and about the development of students' creative abilities. This course is focused on 3D modeling in the AutoCAD package.